Entrepreneurship, stages of development, and industrialization - Zoltan J. Ács; Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Unlike in the past where industrial policy was either focused on creation and growth of state-owned firms or alternatively consisted merely of broadly functional policies without consideration for firm or entrepreneurial specifics, the requirement now is that future industrial policy ought to be a nuanced partnership between entrepreneurs and the state. In this paper we outline some considerations for such an industrial policy where the entrepreneur-state nexus is paramount. Moreover, we argue that such an industrial policy will need to take into consideration that the entrepreneur-state nexus is evolving, and that it depends on the stage of development of a particular country.
Keywords: O32; L52; L53; M13; 330; entrepreneurship; industrialization; structural change; industrial policy; innovation; development; Unternehmer; Entwicklung; Industrialisierung; Industrialisierungspolitik